PENINGKATAN KEMAMPUAN MENGIDENTIFIKASI UNSUR CERITA LISAN MELALUI METODE KUIS PENDIDIKAN INTERAKTIF SISWA KELAS V SD NEGERI 2 PEJAWARAN - Soni Fajarudin; Wahyu Sukartiningsih; Suhartono Suhartono (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2020)
ABSTRACTThis study is a Class Action Research which aims to describe the improvement in the students ability to identify elements of the story which is listened through Interactive Education Quiz methods for 5th grade students of SD Negeri 2 Pejawaran. This study refers to the views of Kemmis and Taggart which were held for two cycles research.  Each cycle consists of planning, acting and observing, and reflecting. The data collection techniques of this research are observation, interviews, questionnaires, and listening skills tests. The data of each cycle were analyzed and tested using one sample paired t-test (Paired Pre-Post Samples t-test). The results of the data analysis of cycle I and cycle II show that the activity of teacher in learning increased of 10,94% and included into Very Good criteria, student activities in learning increased of 6,75% and on average included into Very Active criteria, positive responses of students increased of 3,45% or included into Very Good criteria, and the average of test students' listening stories skills increased of 62,07% with 27 students or 93,10% of students at the end of the second cycle belong to Completed criteria. Based on data analysis, it can be concluded that the application of the Interactive Education Quiz method can increase the activity of teachers and students in learning activities, it also makes teachers and students respond positively to learning, and can significantly improve students skills in identifying the elements of the story that is listened.Keywords: Interactive Education Quiz Method, Listening Skills, Story Element.ABSTRAK                                                                                         Penelitian ini adalah Penelitian Tindakan Kelas yang bertujuan untuk mendeskripsikan peningkatan kemampuan mengidentifikasi unsur-unsur cerita yang didengar melalui metode Kuis Pendidikan Interaktif siswa kelas V SD Negeri 2 Pejawaran. Penelitian ini merujuk pada pandangan Kemmis dan Taggart yang dilaksanakan selama 2 siklus. Setiap siklus terdiri atas tahapan perencanaan, tindakan dan pengamatan, serta refleksi. Teknik pengumpulan data penelitian ini adalah observasi, wawancara, angket, dan tes kemampuan menyimak siswa. Data hasil penelitian tiap siklus dianalisis dan diuji menggunakan uji-t berpasangan satu sampel (Paired Pre-Post Samples t-test). Hasil analisis data siklus I dan siklus II menunjukkan aktivitas guru dalam pembelajaran terjadi peningkatan sebesar 10,94% dan mendapat kriteria Sangat Baik, aktivitas siswa dalam pembelajaran meningkat 6,75% dan secara rata-rata mendapat kriteria Sangat Aktif, respons positif siswa meningkat 3,45% atau mencapai kriteria Sangat Baik, dan rata-rata tes kemampuan menyimak cerita siswa meningkat 62,07% dengan 27 siswa atau 93,10% siswa di akhir siklus II mendapat kriteria Tuntas. Berdasarkan analisis data, dapat disimpulkan bahwa penerapan metode Kuis Pendidikan Interaktif dapat meningkatkan aktivitas guru dan siswa dalam pembelajaran, guru dan siswa merespons positif terhadap pembelajaran, serta dapat meningkatkan kemampuan siswa dalam mengidentifikasi unsur cerita yang didengar secara signifikan.Kata Kunci: Kemampuan Menyimak, Metode Kuis Pendidikan Interaktif, Unsur-Unsur Cerita.